Millimeter Wave Propagation through Plasma - Chakrabarti, S. K.; Akhter, J.; Sinha, R. (Himalayan Physics, 2011)
Theoretical investigation has been carried out to evaluate the attenuation constant and phase velocity of millimetre wave in plasma. For this purpose the expression for the permittivity of plasma medium is obtained. The concept of Faraday rotation has been introduced for utilisation of the same for further calculation. It has been found that attenuation constant and phase velocity both increase with increasing value of plasma frequency. However, the value of attenuation constant decreases with increasing operational frequency. Key words: Plasma; Millimetre wave; Faraday Effect; Attenutation constant; Phase velocity The Himalayan Physics Vol.1, No.1, May, 2010 Page: 34-36 Uploaded Date: 28 July, 2011